2016
DOI: 10.1016/j.jana.2015.11.007
|View full text |Cite
|
Sign up to set email alerts
|

HIV Stigma Toward People Living With HIV and Health Providers Associated With Their Care: Qualitative Interviews With Community Members in Egypt

Abstract: We explored perceived HIV stigma by community members in a low-HIV-prevalence setting toward people living with HIV (PLWH) and physicians associated with HIV in order to develop operational stigma reduction recommendations for HIV referral hospitals. In-depth interviews (N = 30) were conducted with educated and less-educated men and women in Egypt. Thematic analysis was applied to identify drivers, manifestations, and outcomes of stigma. Stigma toward PLWH was rooted in values and fears, manifesting in relucta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…Lastly, we found no interventions with a specific focus on health workers living with a stigmatized disease, and addressing any stigma they may experience from co-workers or through the facility structures. Research has shown that stigma affects healthcare workers, either because of their own health status or as a result of working with stigmatized individuals [100, 101]. The HaTSaH study, an ongoing study in Free State province, South Africa, is addressing this gap through a combination intervention approach that focuses on reducing HIV and TB stigma among health workers towards colleague health workers living with HIV and TB through clinical, structural, and sociobehavioral factors [102].…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, we found no interventions with a specific focus on health workers living with a stigmatized disease, and addressing any stigma they may experience from co-workers or through the facility structures. Research has shown that stigma affects healthcare workers, either because of their own health status or as a result of working with stigmatized individuals [100, 101]. The HaTSaH study, an ongoing study in Free State province, South Africa, is addressing this gap through a combination intervention approach that focuses on reducing HIV and TB stigma among health workers towards colleague health workers living with HIV and TB through clinical, structural, and sociobehavioral factors [102].…”
Section: Discussionmentioning
confidence: 99%
“…PLWH experiences of enacted healthcare stigma are widely documented across the globe. [17][18][19] Large-scale stigma reduction efforts will need to be a cornerstone of planned global efforts to end the AIDS epidemic by 2030 [20].…”
Section: Introductionmentioning
confidence: 99%
“…Engaging in this kind of behavior could be attributed to the lack of HIV-related knowledge, especially regarding modes of transmission, among HCPs causing subsequent fear of acquiring the infection while treating PLHIV. Furthermore, the fear of being stigmatized by their families and communities and concerns about losing their HIV-free patients are primary factors that contribute to providers being reluctant to treat HIV-positive individuals 15,16. Based on the findings of a cross-sectional study in Egypt, out of 529 men and women living with HIV who were interviewed on their experiences with HIV-related S&D, 40% asserted that on attending health care facilities, including dental settings, they do not inform HCPs about their HIV status whereas >50% stated that they were denied service upon revealing they had the infection 17…”
Section: Introductionmentioning
confidence: 99%